1997
DOI: 10.1128/iai.65.11.4515-4524.1997
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Mycobacterium tuberculosis culture filtrate proteins by two-dimensional polyacrylamide gel electrophoresis, N-terminal amino acid sequencing, and electrospray mass spectrometry

Abstract: A number of the culture filtrate proteins secreted by Mycobacterium tuberculosis are known to contribute to the immunology of tuberculosis and to possess enzymatic activities associated with pathogenicity. However, a complete analysis of the protein composition of this fraction has been lacking. By using two-dimensional polyacrylamide gel electrophoresis, detailed maps of the culture filtrate proteins of M. tuberculosis H37Rv were generated. In total, 205 protein spots were observed. The coupling of this elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(80 citation statements)
references
References 62 publications
5
75
0
Order By: Relevance
“…Interestingly, we found 29 M.tb proteins on these exosomes. There are approximately 205 M.tb proteins in the culture supernatant [15] so our findings that 29 of these including ESAT-6 and the 85 complex are trafficked to MVBs and exosomes suggest an efficient transport mechanism. However, why these specific M.tb proteins are targeted is not known.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, we found 29 M.tb proteins on these exosomes. There are approximately 205 M.tb proteins in the culture supernatant [15] so our findings that 29 of these including ESAT-6 and the 85 complex are trafficked to MVBs and exosomes suggest an efficient transport mechanism. However, why these specific M.tb proteins are targeted is not known.…”
Section: Discussionmentioning
confidence: 72%
“…The vast majority of mycobacterial proteins identified on the exosomes are known/predicted to be secreted [15] as summarized in Table 1. Most of the proteins are likely secreted via the SecA secretory system but some such as ESAT-6 are released through the newly described type VII secretion system present in mycobacteria [16].…”
Section: Characterization and Proteomic Analysis Of Exosomes From Mtmentioning
confidence: 99%
“…a-Crystallin spots showing increased intensity on gels of the starved cultures are therefore species with differing pI and molecular weights compared with the most abundant forms. Different species of this protein at lower molecular weights and differing pIs have been observed previously (Sonnenberg and Belisle, 1997;Betts et al, 2000) and could result from degradation, post-translational processing or post-translational modification, such as phosphorylation.…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 67%
“…Tig is a chaperone-like protein homologous to the Bacillus subtilis trigger factor, thought to be involved in protein export. The 45 kDa antigen and MPT64 are both found in culture filtrates of M. tuberculosis (Sonnenberg and Belisle, 1997). The 45 kDa antigen is a glycoprotein (Dobos et al, 1996), which was identified as being recognized by antibodies and producing a delayed-type hypersensitivity (DTH) response in immunized guinea pigs (Romain et al, 1993).…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%
“…To rule out autolysis as a source of the extracellular Sod, the HSP65, which is commonly used as a marker for autolysis [22], was also measured using the monoclonal antibody IT-13 [12]. No HSP65 protein was identi¢ed in the culture supernatant £uids using this antibody (Fig.…”
Section: 2 Lane S)mentioning
confidence: 99%